Yield Test of Hybrid Harapan Chili (Capsicum annuum L.) - Luluk Prihastuti Ekowahyuni; Layla Indah Wulansari (The University of Lampung, 2022)
The purpose of this study was to determine the yield test of the promising hybrid chili (Capsicum anmuum L) at the Leuwikopo Experimental Garden. The research was conducted at the Experimental Garden of IPB Leuwikopo, located in Darmaga District, Bogor Regency, West Java. The implementation of the research consisted of several stages, namely nursery, land management, planting, maintenance, harvesting, disease inoculation and observation. Observations were made on 10 sample plants, which were randomly selected for each replication. The hybrid chili genotypes tested showed the same results as the comparison varieties in qualitative characters, especially flower petal color, flower crown color, fruit shape, fruit skin surface and old fruit color. As well as showing a higher yield than the comparison shown in the F-count test with a significant difference between the hybrid chilies tested and the comparison on the characters of dichotomous height, leaf length, weight per fruit, fruit length, fruit skin thickness, weight of 1000 seeds, age of flowering, marketable harvest, fruit weight per plant and chili fruit production per hectare.Keywords: power test; hybrid chili; IPB experimental garden